Fabrication of 150‐nm AlGaN/GaN field‐plated High Electron Mobility Transistors using i‐line stepper. Issue 24 (26th August 2021) - Ando, Yuji; Makisako, Ryutaro; Takahashi, Hidemasa; Wakejima, Akio; Suda, Jun
Abstract: This article reports a high throughput 150‐nm‐gate AlGaN/GaN high electron mobility transistor (HEMT) process using i ‐line stepper lithography and a thermal reflow technique. Optimizing thermal reflow conditions, fabrication of a 150‐nm gate structure was successfully realized with the initial resist opening of 0.7 μm. AlGaN/GaN field‐plated HEMTs were fabricated on a semi‐insulating SiC substrate by using this process. In spite of unoptimized structures, fabricated 150‐nm gate devices exhibited the maximum drain current of 0.65 A/mm and the gate‐drain breakdown voltage exceeding 200 V. Based on cold HEMT extraction measurements, the average gate length of 187 nm and the standard deviation of 30 nm were obtained on a quarter 4‐in. wafer.